CONVERGE Training Modules: A free online educational tool for hazards and disaster researchers and practitioners - Adams, Rachel M.; Evans, Candace M.; Peek, Lori (Frontiers in Built Environment, 2023)
The National Science Foundation-supported CONVERGE facility was established in 2018 as the first social science-led component of the Natural Hazards Engineering Research Infrastructure (NHERI). Headquartered at the Natural Hazards Center at the University of Colorado Boulder, CONVERGE identifies, trains, connects, and funds researchers across disciplines in the hazards and disaster field. This article provides an overview of one of our most widely used tools, the CONVERGE Training Modules. These free, interactive, online trainings are designed for students, early career professionals, and others who are new to hazards and disaster research and practice. Since July 2019, our team has released 10 modules that cover a range of foundational topics in hazards and disaster research, including Institutional Review Board procedures, conducting emotionally challenging research, cultural competence, collecting and sharing perishable data, social vulnerability, and disaster mental health. In addition, CONVERGE offers advanced trainings in specialized topics such as broader ethical considerations for hazards and disaster researchers, reciprocity, gender-based violence in fieldwork, and public health implications of hazards and disaster research. Between July 2019 and November 2022, 6,311 unique users registered for the modules, and these users logged 7,222 module completions. Of the module completions to date, most users completed only one (46.0%) of the available trainings, although a small group of “superusers”—whom we surveyed for this article—have completed between all or almost all of the available modules. When asked why they planned to complete the modules at the time of registration, most users indicated that it was to fulfill a classroom or other educational requirement (51.2%), for personal interest/to learn more (9.0%), or to prepare for or to support research (7.1%) or practice-oriented activities (5.8%). In addition to providing more information regarding module users, this article details the development of the technology and discusses the impact and success of this tool for transferring knowledge and skills to the hazards and disaster research and practice community. We conclude with a discussion of future directions for this research-based educational intervention.